Making Sense with the Body in Music. The Enlarged Reality of Music Cognition (Revista Argentina de Musicología, 2019)
The question of the nature of music as an object of knowledge underlies the constructs of the analytical and interpretative approaches of music treatises in the Western academy. However, the ontological problem does not end there. A parallel path in the field of music psychology has investigated the experiential dimension of music as a sonic stimulus, together with the mechanisms and processes of perception and action that are involved in the cognition of musical works. It is undeniable that the materiality of the sound perceived and produced defines the musical content. However, an ontology of musical knowledge based only on the construction of percepts fails to provide a full explanation of the status of reality in music cognition. In this paper, the concept of cognitive reality is interrogated at the intersection between the musicological and psychological fields. An imaginative, embodied and dynamic dimension of music cognition is posited. The way the concepts of musical analysis are positively linked to the use of correspondences between different domains of experience is explained with the aim of enhancing the extent of the cognitive reality in musical experience.
Keywords: embodied music cognition; sense making; cognitive reality; musical experience; musical analysis